Odpowiedź :
Odpowiedź:
a)
dla x = 1 1/2, y = - 1/4, z = - 3/8
x - y 1 1/2 - (- 1/4) 1 2/4 + 1/4 1 3/4
--------- = --------------------- = ----------------- = ------------- =
y - z - 1/4 - (- 3/8) - 2/8 + 3/8 1/8
= 1 3/4 : 1/8 = 7/4 * 8/1 = 56/4 = 14
Szczegółowe wyjaśnienie:
[tex]a)\\x=1\frac12\\y=-\frac14\\z=-\frac38\\\dfrac{x-y}{y-z}=\dfrac{1\frac12-(-\frac14)}{-\frac14-(-\frac38)}=\dfrac{1\frac12+\frac14}{-\frac14+\frac38}=\dfrac{1\frac24+\frac14}{-\frac28+\frac38}=\dfrac{1\frac34}{\frac18}=1\frac34:\frac18=\frac74\cdot\frac81=14[/tex]